Historic evidence to support a causal relationship between spirochetal infections and Alzheimer’s disease - Miklossy, Judith (Frontiers in Aging Neuroscience, 2015)
Following previous observations a statistically significant association between various types of spirochetes and Alzheimer’s disease (AD) fulfilled Hill’s criteria in favor of a causal relationship. If spirochetal infections can indeed cause AD, the pathological and biological hallmarks of AD should also occur in syphilitic dementia. To answer this question, observations and illustrations on the detection of spirochetes in the atrophic form of general paresis, which is known to be associated with slowly progressive dementia, were reviewed and compared with the characteristic pathology of AD. Historic observations and illustrations published in the first half of the 20th Century indeed confirm that the pathological hallmarks, which define AD, are also present in syphilitic dementia. Cortical spirochetal colonies are made up by innumerable tightly spiraled Treponema pallidum spirochetes, which are morphologically indistinguishable from senile plaques, using conventional light microscopy. Local brain amyloidosis also occurs in general paresis and, as in AD, corresponds to amyloid beta. These historic observations enable us to conclude that chronic spirochetal infections can cause dementia and reproduce the defining hallmarks of AD. They represent further evidence in support a causal relationship between various spirochetal infections and AD. They also indicate that local invasion of the brain by these helically shaped bacteria reproduce the filamentous pathology characteristic of AD. Chronic infection by spirochetes, and co-infection with other bacteria and viruses should be included in our current view on the etiology of AD. Prompt action is needed as AD might be prevented.